In focus coaching styles - Trikojus, Tom (Bendigo, Victoria : Video Education Australasia, 2003)
Summary: This program looks at the skills a good sport coach is required to posses such as: leadership, management, enthusiasm, and good communication. It also examines three different coaching styles; authoritarian, distant yet approachable and, friendly.
Executive producer, Mark McAuliffe ; editor, Joel De Courcy Browne
narrator: Peter Kent
Keywords: Coaching (Athletics)